History of posterior thoracic instrumentation - Singh, Harshpal; Rahimi, Scott Y.; Yeh, David J.; Floyd, David (Neurosurgical focus, 2004)
The term “backbone” appears in many expressions used in modern day society. In any scenario, it has one central meaning: stability. Best defined as a foundation that is able to sustain multiple stressors without adversely affecting integrity, the commonly and appropriately termed backbone of humans is the spinal column. As the central focus of stability in our species, the spine is subject to a great degree of trauma and mechanical forces. A variety of methods have been developed throughout history in the treatment of spinal column injury. Initial treatment involved the use of simple traction devices for the reduction of spinal fractures; these have evolved to include the current insertion of spinal instrumentation. The authors review the historical treatment and development of posterior instrumentation for thoracic spinal injury.